Role of Village Government in Combating Illegal Gold Mining (PETI) at the Batang Teso Irrigation Dam, Marsawa Village, Riau - Marsa, Lilis Tri; Nasution, Hazqon Fuadi (Program Studi Ilmu Administrasi Negara FISIP UMRAH, 2025)
Illegal gold mining without a permit (PETI) at the Batang Teso Irrigation Dam in Marsawa Village, Kuantan Singingi Regency, Riau Province, has become a serious environmental and social issue due to its destructive impacts and lack of government supervision. The activity not only causes water pollution and ecosystem degradation but also endangers the health and safety of local communities. This research aims to analyze the role and involvement of the village government in mitigating illegal gold mining activities and to identify the collaborative strategies employed to control and prevent PETI in the Batang Teso area. Using a qualitative research approach combined with a literature review and case study method, data were collected through interviews with village officials, security forces, local communities, and related institutions, as well as through document analysis and field observations. The findings indicate that illegal mining has led to severe water contamination caused by mercury waste, the destruction of the irrigation system, and the decline of Batang Teso’s function as a community tourism site. Mitigation efforts have been conducted through cooperation between the village government, the Kuantan Singingi Police (Polres Kuansing), the Indonesian National Armed Forces (TNI), and the Department of Environment. These efforts include strict enforcement actions, socialization programs, public education, and community empowerment to promote alternative livelihoods that are environmentally sustainable. The study concludes that strong synergy between the village government, law enforcement agencies, and the community plays a crucial role in reducing illegal mining activities. Continuous supervision, legal enforcement, and sustainable livelihood programs are essential to protect both the environment and public health around the Batang Teso Irrigation Dam.